Peningkatan Kualitas dan Pemasaran Produk Wedang Rempah Khas Solo Bu Parti - M. Aisy Akbar Firdaus Firdaus; Tri Nur Azizah; Fitra Indah Wiratantri; Sri Devi Rahma Suherman; Iswandi Iswandi (PPPM POLITEKNIK NEGERI SAMBAS, 2023)
The development and empowerment of micro, small and medium enterprises is needed to increase product sales value. The Solo government encourages the micro enterprise sector to develop further, one of the typical Solo enterprise has the potential to produce herbs and spices. The purpose of this activity is to increase people's purchasing for herbs and spices at online platforms. The method of this activity i.e the observation, preparation, implementation and evaluation stages. The results of the activity are shown by the new packaging design and creation of social media accounts as well as evaluation of purchases through the shopee marketplace. Realization of sales training through the shopee marketplace is carried out with training on creating a seller account, how to input goods, item details, promotions, and withdrawing balances from the seller's account.